Model Teaching Factory (Tefa) Berbasis Project-Based Learning Untuk Meningkatkan Kualitas Produk - Dafrid Cahyadi Arifin; Abdul Sakti; Andi Alvian Nur Risal (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine the implementation of a Teaching Factory (TEFA) model based on Project-Based Learning (PjBL) in improving the quality of student products in Vocational High Schools (SMK) in the era of Industry 4.0. The TEFA learning approach emphasizes real production processes aligned with industry standards, while Project-Based Learning focuses on active student involvement in completing authentic projects. This research employed a quantitative approach with a quasi-experimental design. The research subjects were students of SMK Negeri 8 Makassar participating in TEFA-based learning activities. Data were collected through observation, questionnaires, documentation, and product quality assessments. Data analysis was conducted using descriptive statistics and learning outcome improvement tests. The results indicate that the implementation of the TEFA model based on PjBL significantly improves student product quality in terms of technical aspects, creativity, and conformity with industry standards. Moreover, this model positively influences students’ work attitudes, independence, and problem-solving skills. Therefore, the TEFA model based on Project-Based Learning can be considered an effective learning strategy to prepare competent, adaptive, and competitive vocational graduates in the era of Industry 4.0.